PERGESERAN PERAN DOMESTIK PADA KELUARGA TKW DI DESA SASAHAN KECAMATAN WARINGIN KURUNG KABUPATEN SERANG - Rahmawati Rahmawati (Jurnal Administrasi Publik, 2014)
This study aims to determine the shift in domestic role in the family of migrantworkers in Desa Sasahan. Talking about the father figure in the family of migrant workers is tantamount to dissect the role of a husband whose wife left to work abroad and replace domestic roles performed by the wife. The husband / father to be a double play in living family life in his own country. The issue of parenting, education, discipline, family communication to the financial management of the household must be male (husband) family life can be mastered in order to run properly. This study uses descriptive qualitative method. The informants were migrant husband, former migrant workers, migrant families and village. The results showed the economic factor is the main reason women become migrant workers because of the husband's income is not sufficient for the garden everyday needs including cost and school children during family leave, child care role performed by the husband and assisted by a large family of husband / wife, usually parents wife. Financial management result is still held by the wife works and new wife brought when his wife returned to Indonesia used to plan the future of the family.